Phosphorylated nano-diamond/Polyimide Nanocomposites - (:unkn) unknown (IOP PUBLISHING LTD, 2014)
In this study, a novel route to synthesize polyimide (PI)/phosphorylated nano-diamond films with improved thermal and mechanical properties was developed. Surface phosphorylation of nano-diamond was performed in dichloromethane. Phosphorylation dramatically enhanced the thermal stability of nano-diamond. Poly(amic acid) (PAA), which is the precursor of PI, was successfully synthesized with 3,3',4,4'-Benzophenonetetracarboxylic dianhydride (BTDA) and 4,4'-oxydianiline (4,4'-ODA) in the solution of N,N-dimethylformamide (DMF). Pure BTDA-ODA polyimide films and phosphorylated nano-diamond containing BTDA-ODA PI films were prepared. The PAA displayed good compatibility with phosphorylated nano-diamond. The morphology of the polyimide (PI)/phosphorylated nano-diamond was characterized by scanning electron microscopy (SEM). Chemical structure of polyimide and polyimide (PI)/phosphorylated nano-diamond was characterized by FTIR. SEM and FTIR results showed that the phosphorylated nano-diamond was successfully prepared. Thermal properties of the polyimide (PI)/phosphorylated nanodiamond was characterized by thermogravimetric analysis (TGA). TGA results showed that the thermal stability of (PI)/phosphorylated nano-diamond film was increased.
Keywords: MEMBRANES